2015
DOI: 10.1017/s0305000915000641
|View full text |Cite
|
Sign up to set email alerts
|

Sources of variability in language development of children with cochlear implants: age at implantation, parental language, and early features of children's language construction

Abstract: A B S T R A C TThe aim of the present study was to analyze the relative influence of age at implantation, parental expansions, and child language internal factors on grammatical progress in children with cochlear implants (CI). Data analyses used two longitudinal corpora of spontaneous speech samples, one with twenty-two and one with twenty-six children, implanted between ; and ;. Analyses were performed on the combined and separate samples. Regression analyses indicate that early child MLU is the stronge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 51 publications
4
50
0
Order By: Relevance
“…). Overall, what emerges from our data is the contribution of both environmental (mother's language) and individual (age of activation) variables to the language development of children with CIs, with an added contribution about the language development of Italian children, in line with previous studies on this topic (Szagun and Stumper ).…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…). Overall, what emerges from our data is the contribution of both environmental (mother's language) and individual (age of activation) variables to the language development of children with CIs, with an added contribution about the language development of Italian children, in line with previous studies on this topic (Szagun and Stumper ).…”
Section: Discussionsupporting
confidence: 88%
“…Recently, though, Convertino et al (2014) did not find any effect of age at implantation on word knowledge, and Dunn et al (2014), in a longitudinal study using different instruments to assess language outcomes at different age points (annual intervals from 5 to 13 years), showed that the effect of age at implantation (under 2 years versus between 2 and 3.9 years) became weaker with time: the effect on receptive language had disappeared by age 8 and on expressive language by age 10. With regard to this last point, various studies reported considerable variability in the advantage for language development of the lower age of implantation (Convertino et al 2014, Szagun andSchramm 2016) and describe different profiles in children with CIs (de Hoog et al 2016). For example, considering the age at CI activation, some studies found a better language outcome for children whose CI activation occurred at under 12 months of age (Cuda et al 2014, Dettman et al 2016, Leigh et al 2013.…”
Section: Role Of Age At Implantation In Language Productionmentioning
confidence: 99%
See 3 more Smart Citations